The Impact of the Flipped Classroom on Mathematics Concept Learning in High School - Bhagat, Kaushal Kumar; Chang, Cheng-Nan; Chang, Chun-Yen (Educational Technology ＆ Society, 2016)
The present study aimed to examine the effectiveness of the flipped classroom learning environment on learner's learning achievement and motivation, as well as to investigate the effects of flipped classrooms on learners with different achievement levels in learning mathematics concepts. The learning achievement and motivation were measured by the Mathematics Achievement Test (MAT) and Course Interest Survey (CIS), respectively. A pretest posttest quasi-experimental design was employed for this study. A total of 82 high-school students participated in this study, divided into experimental and control groups. The experimental group (41) was taught trigonometry using the flipped classroom method, while the control group (41) was taught by traditional teaching methods. The researchers employed independent sample t-test, analysis of covariance (ANCOVA), and multivariate analysis of variance (MANOVA) to analyze the data obtained. Findings indicated a significant difference in the learning achievement and motivation between the two groups, with students using the flipped classroom performing better. Further analysis showed a significant difference in the performance of low achievers in the experimental and control groups.